LOW MOLECULAR METABOLITES OF FUNGI. 13,24-DIMETOXYSTACHIBOTRIN FROM STACHYBOTRYS CHARTARUM - Lukhmon Sirojiddinovich Kamolov; Suvonkul Erxanovich Nurmanov; Azizbek Asadullo o`g`li Abduraxmonov (International Engineering Journal For Research & Development, 2021)
As a result of studies carried out in our country, information was obtained on the distribution of fungi of the genus Stachybotrys, their morphology, ultrastructure, cytology, biotechnology of cultivation on cellulose-containing nutrient media, ensiling of such solid plant waste as guzapoya, rice straw, corn stalks. Stachybotrys chartarum produces a number of low molecular weight compounds. A technique has been developed for the isolation and separation of the sum of extractive substances - waste products of the fungus Stachybotrys chartarum grown under laboratory conditions on various nutrient media. Cause and formulation of the problem, purpose of the work: The purpose of the study is the selection of active local strains of micromycetes, forming 13,24-dimethoxystachibotrin and stachibotral, the study of their morphological cultural properties, the creation of a complex biological product based on promising local strains that protect against fungal phytopathogens.